THE EFFECT OF MAGNETIC THERAPY AND REHABILITATION EXERCISES ON IMPROVING SOME PHYSICAL AND MOTOR ABILITIES AND REDUCING PAIN IN CHILDREN WITH SEVER'S DISEASE - Amal Dawood Abd-Alhasan (Universitas Negeri Jakarta, 2025)
Background. Sever’s disease is a common cause of heel and ankle pain among children, often linked to excessive sports participation, inappropriate footwear, lack of flexibility, muscle weakness, and excess body weight. Rehabilitation interventions, including magnetic therapy and structured exercises, have shown promise in addressing musculoskeletal disorders; however, their effectiveness in treating Sever’s disease remains underexplored. Objectives. This study aimed to evaluate the effect of magnetic therapy and rehabilitation exercises on improving selected physical and motor abilities and reducing pain in children with Sever’s disease. Method. An experimental design was employed with a purposive sample of 17 children diagnosed with the condition. The intervention program consisted of 25 rehabilitation units delivered over five weeks, at a frequency of five sessions per week. Magnetic therapy sessions and rehabilitation exercises were developed based on pilot testing and subsequently applied to the study group. Pre- and post-tests were conducted to measure physical and motor abilities as well as pain reduction, and the results were analyzed statistically. Results. Findings demonstrated significant improvements in flexibility, strength, motor performance, and pain reduction among participants after the intervention. These outcomes highlight the therapeutic value of combining magnetic therapy with rehabilitation exercises for pediatric patients suffering from Sever’s disease. Conclusion. The study concludes that such an integrative approach is effective for rehabilitation and may be extended to other joint-related conditions. The contribution of this research lies in providing empirical evidence supporting a non-invasive, safe, and accessible treatment protocol that can enhance the quality of life for children with musculoskeletal disorders.